Slow steaming and further emission reductions: A study in collaboration with MAN Energy Solutions - Månsson, Mattias; Johansson, Axel (My University, 2024)
The shipping industry is responsible for a significant amount of the emission emitted into the atmosphere, therefore there is of high importance to reduce both fuel consumption and the emissions. Slow steaming and other fuel reduction strategies has the potential to help reduce the climate impact from shipping. The report uses engine operational data collected from MAN Energy Solutions test facility in Copenhagen, combined with peer reviewed literature studies and IMO commission guidelines. The operational data is from a MAN B&W Two-stroke 7G60ME-C10.5 with SMCR 12100 kW 82 rpm engine. At different operating ranges, emissions of NOx, SOx, CO, and CO2 are examined to determine which emissions increase and which decrease at different loads to select operating modes to reduce both fuel consumption and emissions. In addition, which fuels, engine tuning (Tier II or Tier III) that complies with the laws and regulations implemented by IMO. For the examined engine it is shown that operating the engine at 65% load, the fuel to power ratio will be optimal, while considering further emission reduction loads below 65% will always produce less emission due to lower engine fuel demand. The limitations of this report are as follows: the report only examines the engine's exhaust emissions and does not implement exhaust gas aftertreatment systems, the report does not consider external factors such as wind, waves, water currents, or other weather conditions; the report also does not examine how slow steaming affects the engine in terms of wear and tear.
Keywords: Slow steaming; Bränsleförbrukning; Utsläpp; Utsläppsminskning; Slow steaming; Fuel consumption; Emissions; Emission reduction